Chaos synchronization and parameters estimation of chaotic Lur'e systems with full unknown parameters via sampled-data control. (13th May 2017) - Gao, Xiaojing; Hu, Hanping
Abstract: In this article, we investigate the parameters estimation and chaos synchronization problem for chaotic Lur'e systems based on the sampled-data control method, adaptive control and Lyapunov stability theory. An adaptive parameters update rule and a sampled-data controller are constructed by using sampled-data drive signals to realize the parameters estimation and chaos synchronization. Different from existing sampled-data control strategies, all parameters of the Lur'e systems are unknown in our article, which is more reasonable in applications. The corresponding theoretical proof is given to guarantee the effectiveness of the proposed strategy. Finally, numerical examples are given to show the effectiveness of the proposed method.